Promoting physical activity in physical therapy practice: therapists' knowledge, attitudes, and practices. - Alshehri, Nuha S.; Alzahrani, Hosam (Journal of Public Health: From Theory to Practice (2198-1833), 2026)
Aim: This study aimed to assess physical therapists' knowledge, confidence, and attitudes toward promoting physical activity (PA) in their clinical practice and the barriers they encounter when providing such counseling. Methods: This cross-sectional survey included Saudi physical therapists and students. The questionnaire covered the following: knowledge of PA guidelines, confidence and perceptions about promoting PA, barriers to PA promotion, and the feasibility of different PA promotion strategies. Students answered the same questionnaire, excluding questions on barriers and counseling practices. Results: This study included 420 participants, 56.2% of whom were students. Nearly half the therapists reported their ability to correctly describe the WHO PA guidelines. Awareness of these guidelines was significantly higher among practicing therapists (64.7%) compared to bachelor's students (44.3%). Almost all therapists viewed it as part of their job to encourage patients to become more physically active. Approximately 44% of the therapists frequently counseled patients to increase their activity levels, and they were more likely to feel confident providing general advice on an active lifestyle or suggesting PA programs. Most therapists saw potential in including brief counseling on PA during treatment sessions. Overall, few therapists reported encountering obstacles when trying to encourage patients to engage in PA. Conclusions: Physical therapists and students were knowledgeable about PA guidelines and saw promoting them as part of their role. Therapists who frequently counseled patients on PA were more confident and viewed brief counseling during treatment as feasible. Few therapists perceived barriers to promoting PA, suggesting potential for integrating it into clinical practice.